2015
DOI: 10.1038/mt.2015.77
|View full text |Cite
|
Sign up to set email alerts
|

Bioengineering Thymus Organoids to Restore Thymic Function and Induce Donor-Specific Immune Tolerance to Allografts

Abstract: One of the major obstacles in organ transplantation is to establish immune tolerance of allografts. Although immunosuppressive drugs can prevent graft rejection to a certain degree, their efficacies are limited, transient, and associated with severe side effects. Induction of thymic central tolerance to allografts remains challenging, largely because of the difficulty of maintaining donor thymic epithelial cells in vitro to allow successful bioengineering. Here, the authors show that three-dimensional scaffold… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
100
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 99 publications
(101 citation statements)
references
References 70 publications
1
100
0
Order By: Relevance
“…In this technique, all cells are removed from the organ, leaving the extracellular matrix intact. It has been reported that decellularization of the thymus, followed by reconstitution with thymic stromal cells and lineage negative BM progenitors, led to formation a functional thymus when transplanted into the kidney capsule of nude mice (192). …”
Section: Exogenous Strategies To Enhance Thymic Recoverymentioning
confidence: 99%
“…In this technique, all cells are removed from the organ, leaving the extracellular matrix intact. It has been reported that decellularization of the thymus, followed by reconstitution with thymic stromal cells and lineage negative BM progenitors, led to formation a functional thymus when transplanted into the kidney capsule of nude mice (192). …”
Section: Exogenous Strategies To Enhance Thymic Recoverymentioning
confidence: 99%
“…Monitor the development of T cells in the periphery by harvesting 50–100 ”l blood samples into the EDTA-containing blood collection tube from the nude mice 4–6 weeks post transplantation and stain with a cocktail of anti-CD4, -CD8, -CD45, and -CD3 antibodies 12 .…”
Section: Protocolmentioning
confidence: 99%
“…Analyze the percentages of T-lymphocytes in the peripheral blood leukocytes with flow cytometry (FCM), using single cell analysis software 12 .…”
Section: Protocolmentioning
confidence: 99%
See 1 more Smart Citation
“…Limited, but encouraging functional recoveries of the engineered organoids have been observed in preclinical studies[19, 20]. Taking advantage of the tissue engineering approach, we have reconstructed thymus organoids by repopulating decellularized thymus scaffolds with isolated TECs[21]. The thymus organoids can support T-cell development both in vitro and in vivo .…”
Section: Introductionmentioning
confidence: 99%